Adaptation of The Career Decision Ambiguity Tolerance Scale - Dian R Sawitri; Novi Qonitatin; Ika Febrian Kristiana; Unika Prihatsanti; Kholifah Umi Sholihah; Talitha Lintang Pertiwi (Universitas Ahmad Dahlan, 2023)
The COVID-19 pandemic has led to various changes that increased a possibility for university students to experience career ambiguity. Those with a high tolerance for career ambiguity perceive ambiguous situations as advantageous and do not reject the complexity of the discrepancy. This study aimed to yield the Indonesian version of the Career Decision Ambiguity Tolerance Scale and examine the construct validity and concurrent validity of the adapted version. This study involved 1256 first-year students (58.7% female, mean age = 18.23 years, SD age = .66) from a public university in Central Java, Indonesia. Data were collected using measures of ambiguity tolerance in choosing a career, career decision-making self-efficacy, and vocational identity. Confirmatory Factor Analysis (CFA) was used to examine the structure of the factor of the final scale, showing good fit indices (CMIN/df = 2.93, CFI = .97, TLI = .96, RMSEA = .04). Reliability coefficients of each the three subscales were satisfactory. Concurrent validity was shown by expected associations with measures of career decision-making self-efficacy and vocational identity.